Pengaruh Shopping Lifestyle, Fashion Involvement Dan Promosi Penjualan Terhadap Pembelian Impulsif (Studi Pada Mahasiswa S-1 Universitas Islam Malang Angkatan Tahun 2019 Yang Pernah Berkunjung Ke Deliwafa Store Malang) - Ifni Igne Zulcha; Muhammad Ridwan Basalamah; Muhammad Tody Arsyianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of Shopping Lifestyle, Fashion Involvement and Sales Promotion on Impulsive Buying. Sampling in this study used Nonprobability Sampling, namely, a sampling technique that does not provide equal opportunities or opportunities for each element or member of the population to be selected as a sample. The sample in this study was 85 respondents who were undergraduate students at the Islamic University of Malang class of 2019. The analysis technique used multiple linear regression analysis. The results of this study indicate that partially each of the variables Shopping Lifestyle, Fashion Involvement, and Sales Promotion both have a positive effect on Impulsive Buying, while simultaneously the variables Shopping Lifestyle, Fashion Involvement, and Sales Promotion also have a positive effect on Impulsive Buying. Keywords: Shopping Lifestyle, Fashion Involvement, Sales Promotion, Impulsive Buying